2013
DOI: 10.1371/journal.pone.0073239
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Correlations in Stride Intervals May Emerge from Non-Chaotic Walking Dynamics

Abstract: Stride intervals of normal human walking exhibit long-range temporal correlations. Similar to the fractal-like behaviors observed in brain and heart activity, long-range correlations in walking have commonly been interpreted to result from chaotic dynamics and be a signature of health. Several mathematical models have reproduced this behavior by assuming a dominant role of neural central pattern generators (CPGs) and/or nonlinear biomechanics to evoke chaos. In this study, we show that a simple walking model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 39 publications
(91 reference statements)
0
34
0
Order By: Relevance
“…Fourteen subjects [5 females, 9 males; mean age = 18.7 (18)(19)(20)(21) years] participated in experiment 1, 18 subjects [7 females, 11 males; mean age = 19.1 (18)(19)(20)(21) years] participated in experiment 2, and 12 subjects [5 females, 7 males; mean age = 20.0 (18)(19)(20)(21)(22) years] participated in experiment 3. Data from two subjects in experiment 1 were excluded because their average stepping accuracy across all conditions was more than 2 SDs from the mean.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen subjects [5 females, 9 males; mean age = 18.7 (18)(19)(20)(21) years] participated in experiment 1, 18 subjects [7 females, 11 males; mean age = 19.1 (18)(19)(20)(21) years] participated in experiment 2, and 12 subjects [5 females, 7 males; mean age = 20.0 (18)(19)(20)(21)(22) years] participated in experiment 3. Data from two subjects in experiment 1 were excluded because their average stepping accuracy across all conditions was more than 2 SDs from the mean.…”
Section: Methodsmentioning
confidence: 99%
“…As such, a small forward perturbation applied to the COM at midstep increases the speed of the COM, which in turn increases the collision loss so the additional energy that is injected into the system by the perturbation will be dissipated at collision (15). Although the basin of attraction for bipedal gait may be relatively shallow, spinal-level reflex pathways (3) may serve to facilitate gait-restorative responses that take advantage of this passive stability (18)(19)(20). † Active Control of Walking These insights imply that certain desirable characteristics of movement, such as coordination, efficiency, and stability, can emerge without active (i.e., perceptually guided) control.…”
Section: Significancementioning
confidence: 99%
“…The limited number of ARMA parameters contradicts conclusions in [17] and recently in [1]. These studies showed a stride intervals of normal human walking which exhibit long-range temporal correlations.…”
Section: Estimatormentioning
confidence: 73%
“…Interestingly, adding variability decreases the average walking speed for a symmetric healthy model (Table III, [46]) but has little to no effect on the average walking speed for the asymmetric amputee model. Since one of the major causes of the reduced speed for healthy gait is likely reduced stance ankle work, the consistent prosthesis ankle work combined with a natural persistence of temporal perturbations [50] may be enough to prevent a reduction in speed for the human-prosthesis system.…”
Section: Simulationmentioning
confidence: 99%